2018
DOI: 10.1007/s11606-018-4622-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Personalized Breast Density and Breast Cancer Risk Notification

Abstract: Brief, personalized videos following mammography can improve knowledge of MBD and personal risk of breast cancer compared to a legislatively mandated informational letter. Trial Registration Clinicaltrials.gov (NCT02986360).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…One qualitative study of Spanish-speaking women in Massachusetts demonstrated that among women with no previous knowledge of breast density who received notification letters in English, the result was confusion and misinterpretation. 29 Other studies examining the method of breast density information delivery found an increase in knowledge of breast density for women who were shown a short, personalized video after mammography 30 as well as increased rates of supplemental ultrasound screening in women whose notification letters were followed by a courtesy call. 31 Our study had a high response rate; however, our survey may be affected by a self-selection bias, and nonresponders may be different from responders in terms of their activities around breast density legislation.…”
Section: Discussionmentioning
confidence: 99%
“…One qualitative study of Spanish-speaking women in Massachusetts demonstrated that among women with no previous knowledge of breast density who received notification letters in English, the result was confusion and misinterpretation. 29 Other studies examining the method of breast density information delivery found an increase in knowledge of breast density for women who were shown a short, personalized video after mammography 30 as well as increased rates of supplemental ultrasound screening in women whose notification letters were followed by a courtesy call. 31 Our study had a high response rate; however, our survey may be affected by a self-selection bias, and nonresponders may be different from responders in terms of their activities around breast density legislation.…”
Section: Discussionmentioning
confidence: 99%
“…19 One tool to provide personalized risk information based on the BCSC's breast cancer risk calculator in combination with breast density notification improved women's knowledge and recognition of risk and prompted them to discuss options with their primary care providers (PCP). 20 More research is needed to understand the tool's usefulness for women from a variety of backgrounds, how prepared PCPs or other providers are to answer questions or assist women in making decisions, [21][22][23] and impacts on subsequent screening.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of breast density and its relationship to increased breast cancer risk 18 and a reduction of sensitivity of mammography 22 are evidenced by mammographic breast density (MBD) notification laws in the United States mandating the reporting of mammographic breast density in 32 states. 22 Insurance cover in six of the abovementioned states is also mandated for supplemental screening. 23 Mammography providers in PNG do not routinely report on breast density or notify women of their individual breast density, nor is supplemental screening (MRI, ultrasound or tomosynthesis) routinely encouraged.…”
Section: Breast Densitymentioning
confidence: 99%
“…The Tabár classification system categorises five types of parenchymal patterns: Patterns I, II and III are associated with a low risk for malignancy while Patterns IV and V have a high risk. The importance of breast density and its relationship to increased breast cancer risk 18 and a reduction of sensitivity of mammography 22 are evidenced by mammographic breast density (MBD) notification laws in the United States mandating the reporting of mammographic breast density in 32 states 22 . Insurance cover in six of the abovementioned states is also mandated for supplemental screening 23 .…”
Section: Introductionmentioning
confidence: 99%